FE-NI ALLOY FOR LEAD FRAME AND ITS PRODUCTION - TAKEMOTO TOSHIHIKO; FUJINO TSUTOMU; YAMAZAKI KAZUNOBU (1994)
PURPOSE:To obtain an Fe-Ni alloy for lead frame showing superior plating suitability and solder-wettability even if activation pretreatment is omitted. CONSTITUTION:This alloy is an Fe-Ni alloy which contains, by weight, <=0.05% C, <=0.5% Si, <=1.0% Mn, <=1.0% Cr, 25-50% Ni, and <=0.03% N and where B content is limited to <=0.002%. Further, Si concentration in a surface film is controlled to <=5 atomic % in this alloy. This Fe-Ni alloy is finish-annealed in a reducing atmosphere at >=890 deg.C after cold-rolling so that Si concentration in the surface film becomes <=5 atomic %.